(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Most of the multi-storey buildings are analysed based on an assumption that the structure is subjected to whole load after modeling the entire structure. But in reality, each storey is subjected to some assumed loads to act during construction period itself as they are constructed in stages as storey wise. Sequential analysis in a structure is ignored by many structural engineers while analysing the structure. Because of this ignorance, variation may occur in structural members in the below storey with respect to above storey as the construction proceeds which leads to incorrect distribution of forces in the member. So, analysis has to be done only by sequential application of loads in each storey for the safety of the structure and cost effectiveness. In order to study the structural behavior of a 10-storey building with mass irregularity has been modeled and analyzed by equivalent static method using different structural systems in CSI ETABS V16 as per NBC 105:2020. Finally, results such as axial force, shear force, overturning moment are drawn for the structural members and response such as storey displacement, storey shear and storey drift are plotted and compared for each structural system